Efektifitas Layanan Bimbingan Kelompok Teknik Diskusi untuk Meningkatkan Motivasi Belajar Matematika Siswa Kelas XI SMA Istiqamah Muhammadiyah Samarinda Tahun Ajaran 2025/2026 - Kasri; Yasintha Sari Pratiwi; Rury Muslifar (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to determine the effectiveness of group guidance services using discussion techniques in increasing the motivation to learn mathematics for class XI students at SMA Istiqamah Muhammadiyah. The background of this study was the low motivation to learn mathematics for students, characterized by a lack of interest and enthusiasm in following mathematics lessons, as well as low student learning outcomes. Group guidance services using discussion techniques were chosen as an intervention because this method is believed to increase motivation through discussion, interaction, and support between students. The following study used an experimental method with a pretest-posttest design, with subjects from class XI students, selected by purposive sampling. The data collection instrument was a learning motivation questionnaire given before and after the implementation of group guidance services using discussion techniques. Data were analyzed using the N-Gain test to measure the increase in student learning motivation after participating in the service. The results showed that group guidance services using discussion techniques had a significant influence on increasing student motivation to learn mathematics. The results of the N-Gain test showed a significant increase in student learning motivation after being given group guidance services using discussion techniques. Based on these findings, group guidance services using discussion techniques were proven to be effective in increasing student learning motivation, especially in mathematics.